Discourse framework and reshaping path of British media report on Chinese Confucius Institutes - Leiya Tian (International Journal of Education and Humanities, 2025)
The historical differences between China and Western countries and the dominant discourse of Western media have led to doubts and biases in international public opinion regarding the reporting of Confucius Institutes. The British media serves as a typical example of shaping this negative perception. This study aims to analyze how major British media outlets frame reports on Confucius Institutes using the theory of framing analysis. Through an examination of seven major news media in the United Kingdom, the study finds that reporting on Confucius Institutes is primarily framed within three core themes: the "China threat theory," "Chinese government autocracy," and "controversy surrounding Confucius Institutes." Overall, the media narratives tend to be negative. By applying the concept of "frame device" within Gamson's "interpretive package" theory, the study reveals that behind the negative public opinion of Confucius Institutes in the UK, there are underlying factors such as the dominance of Western media discourse, Western concerns over Chinese cultural influence, and operational challenges faced by Confucius Institutes on a global scale. Based on these findings, the study recommends strategies for optimizing and reshaping the international public image of Confucius Institutes. These strategies include fostering pluralistic dialogue between China and Western countries, implementing more localized management of Confucius Institutes, and promoting a positive international communication agenda for Confucius Institutes. By enhancing the effectiveness of China’s global communication efforts, Confucius Institutes can mitigate misunderstandings and establish a more objective and balanced image on the international stage